Molecular survey of Ehrlichia canis in blood and ticks collected from stray dogs in Kuala Lumpur, Malaysia - Anurddin, Siti Hawa; Watanabe, Malaika (2010)
Ehrlichia canis is the etiological agent of canine monocytic ehrlichiosis, a potentially fatal disease of dogs and is transmitted by the brown dog tick, Rhipicephalus sanguineus. Recent studies have detected other possible tick vectors. Thus far, only one study has been carried out to determine the prevalence of E.canis using molecular methods and there are as yet no study to that detects the organism in ticks in Malaysia. Polymerase chain reaction (PCR) is known to be a sensitive and specific method for the diagnosis of canine ehrlichiosis and currently is the diagnostic method of choice worldwide. Polymerase chain reaction was performed using a species-specific set of primers for the detection of E.canis in blood and ticks collected from 60 stray dogs from Dewan Bandaraya Kuala Lumpur. Out of a total of 122 ticks, 120 were identified as Rhipicephalus sanguineus and two were identified as Haemaphysalis sp. E.canis DNA could not be amplified from any of the 60 canine blood samples or the 60 tick samples.